Walking a Tightrope: Turkey Between the EU and Russia in the Crimea Crisis - TÜRKDOĞAN, SEYYİDE SENA (Uluslararası İlişkiler Konseyi Derneği, 2023)
The Crimea crisis marked one of the latest critical points in the European Union (EU)-Turkey-Russia triangle. This article analyzes Turkey's position between the EU and Russia, after the events that unfolded in February 2014, by adopting Holsti's role theory. Developing a research map through official documents, this article assesses Turkey's two-sided strategic position, by asking the following question: How did Turkey's intertwined relationships with the EU and Russia affect its foreign policy formulation in the Crimea crisis? Turkey's role formulation during the Crimea crisis is defined by empirical data acquired through the official documents of EU institutions and the Turkish and Russian foreign policy ministries. MAXQDA software was utilized to provide a systematic qualitative analysis of the 123 official declarations. This article argues that Turkey's response to the Crimea crisis was affected by several factors stemming from its asymmetric relationship with Russia, its EU candidate status, and kinship with the Crimean Tatars.
Keywords: Crimea Crisis; Turkey-EU Relations; Turkey-Russia Relations; Turkish Foreign Policy; Role Theory